2020
DOI: 10.3390/nu12102991
|View full text |Cite
|
Sign up to set email alerts
|

Do Interventions with Diet or Dietary Supplements Reduce the Disease Activity Score in Rheumatoid Arthritis? A Systematic Review of Randomized Controlled Trials

Abstract: The aim was to compile the evidence from Randomized Controlled Trials (RCTs) of diet or dietary supplements used to reduce disease activity in adults with Rheumatoid Arthritis (RA). Searches were performed in the databases PubMed, Scopus and Cochrane. Only RCT studies of diets, foods or dietary supplements, looking at effects on the Disease Activity Score in 28 joints (DAS28) among adults with RA, published in peer-reviewed journals, were included. A total of 27 articles were included—three of whole diets (Med… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
37
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(45 citation statements)
references
References 58 publications
1
37
0
1
Order By: Relevance
“…There is suggestive but insufficient evidence for a positive impact of the Mediterranean diet on RA-related outcomes (i.e., pain, physical function, disease activity), as reported by a 2009 Cochrane review and recently confirmed by two systematic reviews on the role of Mediterranean diet in RA patients [ 36 , 37 , 38 ]. In particular, a RCT found that a 12 week Mediterranean diet could reduce disease activity (mainly tender joints and general health) but was unable to rescue physical function or morning stiffness [ 39 ]. McKellar et al compared written information and cooking classes as means of Mediterranean diet implementation in women with RA living in socially deprived areas, showing a modest improvement in a number of measures of disease activity [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…There is suggestive but insufficient evidence for a positive impact of the Mediterranean diet on RA-related outcomes (i.e., pain, physical function, disease activity), as reported by a 2009 Cochrane review and recently confirmed by two systematic reviews on the role of Mediterranean diet in RA patients [ 36 , 37 , 38 ]. In particular, a RCT found that a 12 week Mediterranean diet could reduce disease activity (mainly tender joints and general health) but was unable to rescue physical function or morning stiffness [ 39 ]. McKellar et al compared written information and cooking classes as means of Mediterranean diet implementation in women with RA living in socially deprived areas, showing a modest improvement in a number of measures of disease activity [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, this association was partially mediated by BMI [ 41 ]. Studies in other populations have also confirmed Mediterranean diet reduced risk of RA in smokers [ 42 ] as well as RA disease activity [ 43 ], whereas a Western dietary pattern increased risk of RA [ 44 ]. More research is needed to determine which components of these dietary patterns mediate the association with RA, and to what degree diet may mediate the association between obesity and RA.…”
Section: Dietmentioning
confidence: 99%
“…Despite the number of trials that have explored different diet and nutrient supplementation approaches, specific dietary recommendations and evidence-based dietary guidelines for this population are lacking. A recent systematic review concluded that the evidence for the effects of diets and dietary supplements on the Disease Activity Score in 28 joints (DAS28) in people with RA is insufficient and conclusions may not be drawn [13]. Similarly, another review evaluating the effects of diets, dietary supplements, and fasting in RA established that the effectiveness of and need for diets and dietary supplements in RA remains unclear as the responses to diets and supplements vary from one person to another [14].…”
Section: Introductionmentioning
confidence: 99%
“…Although multiple systematic reviews have explored the effectiveness of dietary interventions in RA [13][14][15], no systematic review has focused explicitly on dietary interventions either alone or in combination with omega-3 PUFAs supplementation in this area. Therefore, the aim of this systematic review is to examine the effects of different dietary interventions, with or without omega-3 supplementation for the management of RA.…”
Section: Introductionmentioning
confidence: 99%